2017
DOI: 10.1007/s40071-017-0153-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary zinc requirement of Siberian sturgeon (Acipenser baerii, Brandt 1869) juveniles, based on the growth performance and blood parameters

Abstract: This study investigated the effect of dietary Zn levels on growth performance, feed utilization, and hematological parameters of juvenile Siberian sturgeon (Acipenser baerii, Brandt 1869). The five semipurified diets were formulated by adding 0, 5, 10, 20, and 40 mg Zn kg -1 diet in the form of zinc sulfate (ZnSO 4 ) to provide the actual dietary value of 14.7, 20.8, 27.3, 37.7, and 46.4 Zn kg -1 diet, respectively. The results showed that dietary Zn elevating level significantly improved the growth and feed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 55 publications
4
8
0
Order By: Relevance
“…Nevertheless, no obvious mortality rate were found in present study, similar to Moazenzadeh et al. (), which indicated that basal diet (28.31 mg Zn per kg) met the minimum requirement of grouper. There was a descending tendency in the high‐dose group (80–160 mg Zn per kg) with whatever the source was, which may be explained by the fact that high level of zinc restrains the absorption of other minerals such as Mn, Cu, Fe, Ca, Mg (Clearwater, Farag, & Meyer, ; Gonzalez et al., ; Huang et al., ; NRC, ).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Nevertheless, no obvious mortality rate were found in present study, similar to Moazenzadeh et al. (), which indicated that basal diet (28.31 mg Zn per kg) met the minimum requirement of grouper. There was a descending tendency in the high‐dose group (80–160 mg Zn per kg) with whatever the source was, which may be explained by the fact that high level of zinc restrains the absorption of other minerals such as Mn, Cu, Fe, Ca, Mg (Clearwater, Farag, & Meyer, ; Gonzalez et al., ; Huang et al., ; NRC, ).…”
Section: Discussionsupporting
confidence: 89%
“…Dietary requirement of zinc varied from fish species: 17.0 mg Zn per kg (as ZnSO 4 ·7H 2 O) diets for the minimum zinc requirement of hybrid striped bass Morone chrysops × Morone saxatilis (Buentello et al., ), 55.1 mg/kg dietary zinc (as ZnSO 4 ·7H 2 O) for juvenile grass carp ( Ctenopharyngodon idella ) (Liang et al., ), 37.2 and 52.1 mg zinc per kg (as ZnSO 4 ·7H 2 O) diet for Nile tilapia ( Oreochromis niloticus ) (Huang et al., ) and 29.15 mg/kg dietary zinc (as ZnSO 4 ·5H 2 O) for Siberian sturgeon juveniles (Moazenzadeh et al., ). Interestingly, Chen et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…He added that clove oil (extracted from the plant Eugeaia caryaphyllata) is a local product, safe, effective, and cheap narcotic agent well recommended for fish narcosis. Moazenzadeh et al (2017) investigated the effect of dietary Zn levels (0, 5, 10, 20, and 40 mg Zn /kg) on hematological parameters of juvenile Siberian sturgeon (Acipenser baerii, Brandt 1869). Erythrocyte number, Hb concentration, and Hct were increased with raising dietary Zn level (P≤0.05), whereas a regular trend was not observed in blood indices, including MCV, MCH, and MCHC.…”
Section: Discussionmentioning
confidence: 99%